ASSOCIATION BETWEEN CHRONIC STRESS AND THE INTENSITY AND RECURRENCE OF PSORIATIC SYMPTOMS - Aleksandra Ewa Basak,; Konrad Strużek,; Agnieszka Kwiatkowska,; Ewelina Mączka,; Wiktor Tracz,; Patrycja Świercz,; Kinga Teper,; Sandra Khiralla-Gawlik,; Aleksandra Anna Strzelecka, (International Journal of Innovative Technologies in Social Science, 2025)
Psoriasis is a chronic inflammatory skin disease that significantly impairs quality of life and often presents with systemic manifestations. While its exact etiology remains unclear, stress is increasingly recognized as a major factor in triggering and exacerbating the disease. This paper reviews the current scientific literature on the complex bidirectional relationship between psychological stress and psoriasis, with particular focus on the underlying neuroendocrine mechanisms and clinical consequences. Dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis and the sympathetic–adrenal–medullary (SAM) system plays a key role in stress-related immune activation, promoting inflammation and impairing skin barrier function. Patients identified as "stress responders" experience more frequent and severe flare-ups and often show reduced responsiveness to standard dermatologic therapies. Moreover, the visible and chronic nature of psoriatic lesions contributes to emotional distress, forming a vicious cycle of stress and symptom aggravation. Integrative therapeutic approaches—including relaxation techniques, psychotherapy, and pharmacological treatment with antidepressants or anxiolytics—have demonstrated potential in reducing symptom severity and improving patient well-being. These findings support the implementation of a multidisciplinary model of care that addresses both dermatological and psychological dimensions of psoriasis for more effective, patient-centered management.